Does SCM Moderate the Relationship of Emotional Intelligence, Work Discipline and Job Stress with Organizational Citizenship Behavior? - Sarton Sinambela (International Journal of Supply Chain Management, 2020)
The prime aim of this investigation is to examine the relationship between emotional intelligence, job stress, work discipline, and organizational citizenship behavior with the moderating effect of supply chain management. The method used in this research is descriptive method. The SEM was employed in this investigation. The results showed emotional intelligence does not have an effect on job stress. Emotional intelligence significant positive effect on organizational citizenship behavior (OCB). Emotional intelligence significant positive effect on employee performance. Work discipline significant negative effect on job stress. Work discipline significant positive effect on OCB. Work discipline significant negative effect on employee performance. Job stress significant negative effect on OCB. Job stress does not have an effect on employee performance. OCB significant positive effect on employee performance. Supply chain management significantly and positively inserts moderating effect among the relationship between emotional intelligence, job stress, work discipline, and organizational citizenship behavior.